Peningkatan Kemampuan Penalaran dan Pemahaman Konsep Siswa Melalui Pendekatan Scientific Terintegrasi pada Model Pembelajaran Problem Based Learning (PTK pada Siswa Kelas X TAV-A Semester Genap SMK Negeri 2 Surakarta Tahun 2014/2015) - Rahmawati, Ika Fitria; , Dra. Sri Sutarni, M.Pd (2015)
The purpose of this research is to improve the ability of reasoning and understanding of the concept of class X TAV-A C SMK Negeri 2 Surakarta through the implementation of an integrated approach to the Scientific learning model Problem Based Learning. This study includes classroom action research. Class X TAV-A acts as a receiver and as a mathematics teacher giver action. Data collection methods used were observation, field notes, interview, test, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion. Results of the study showed an increase in the ability penalarandapat views of 1) students filed allegations and provide feedback on (25%) increased to (78.125%), 2) the students compile evidence, giving reasons or evidence of the correctness of the solution (25%) increased to (81.25%), 3) students draw conclusions from the study of (34.375%) increased to (75%). There is an increasing understanding of the concept of students can be seen from 1) students write and apply the formula to the right of (34.375%) increased to (84.375%), 2) students to give examples and not an example of a concept of (31.25%) increased to ( 78.125%), 3) students apply concepts or algorithms in solving the problem of (31.25%) increased to (75%). Based on this study, it was concluded that the approach Scientific integrated in the learning model Problem Based Learning in mathematics learning can improve reasoning skills and understanding of the concept.